Sexualité lesbienne et catégories de genre - Line Chamberland; Julie Théroux-Séguin (Genre, Sexualité et Société)
This article is based on the qualitative part of a study about the social integration of lesbians and gays in their work environment in Quebec. According to a series of semi-directed interviews, the most frequent stereotypes and prejudices about lesbians are related to gender and sexuality. On the one hand, masculinity, or inverted gender, still operates as a signifier of a lesbian identity; on the other hand, lesbian sexuality is interpreted through the sexist stereotypes of the Mother (denial of sexuality) and of the Whore (eroticization thereof). The recurrence of these patterns shows the extent to which heteronormativity has entered the workplace and illustrates the difficulty of thinking about lesbianism without resorting to binary gender and sexual categories. For lesbian workers, it means that it is not easy to retort to stereotyped and prejudiced comments while deconstructing, rather than reproducing, postulate of the heteronormative matrix.